2021
DOI: 10.1016/j.heliyon.2021.e06183
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of immunomodulation by crude polysaccharide from okra against carcinogenic liver injury in mice

Abstract: Polysaccharides have long been recognized as the anticancer agent with low toxicity and slight side effects. Okra (Abelmoschus esculentus L.), a flowering plant from the Malvaceae family that is found in tropical, subtropical, and warm temperate regions around the world. Hence, no in vivo studies have addressed the anticancer and immunomodulatory potential of polysaccharides from okra pods grown in Indonesia. This study aims to investigate the effect of okra raw polysaccharide extract (ORPE) to immune cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Research has established that the pectic polysaccharides of Momordica charantia could inhibit the oxidative stress of liver cells induced by sodium arsenite [ 10 ]. Besides, numerous studies have demonstrated that polysaccharides regulate immunity and protect the liver [ 11 , 12 ]. Hence, our study explored effective and side effect-free hepatoprotective regimens from natural active products to manage chronic As poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Research has established that the pectic polysaccharides of Momordica charantia could inhibit the oxidative stress of liver cells induced by sodium arsenite [ 10 ]. Besides, numerous studies have demonstrated that polysaccharides regulate immunity and protect the liver [ 11 , 12 ]. Hence, our study explored effective and side effect-free hepatoprotective regimens from natural active products to manage chronic As poisoning.…”
Section: Introductionmentioning
confidence: 99%
“… 16 In this study, HCC was induced by the carcinogen diethyl-nitrosamine (DEN), which can cause severe liver damage leading to the accumulation of reactive oxygen species (ROS), oxidative DNA damage, and ultimately lead to cancer. 17 The combination of AgNPs and GEM has not been studied before in the treatment of HCC. Combining nanoparticles with traditional chemotherapy can improve treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…
Abelmoschus esculentus L., also known as okra, coffee okra and "horn bean", is an annual herbaceous flowering plant native to Africa. Okra is generally eaten as a healthy fruit, which is rich in vitamin C and polysaccharides (Hayaza et al, 2021). As a by-product of okra's seed harvest, lignified okra was always thrown away as waste and had not been fully exploited.
…”
mentioning
confidence: 99%